Patient satisfaction with medication therapy adherence clinic services in a district hospital: a cross-sectional study - Yi C. Sim; Intan S. Mohd-Rosli; Boon T. Lau; Siew Y. Ng (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Patient satisfaction is one of the essential indicators for assessing the quality of healthcare services being delivered, including pharmacy ambulatory care service, as it determines the practicability and sustainability of the service provided. As such, pharmaceutical care services provided during medication therapy adherence clinic (MTAC) sessions need to be assessed to maximise its effectiveness and benefits to the patients. Objective: This study aimed to assess the association between patient satisfaction and socio-demographic characteristics, as well as the predictors for patient satisfaction. Methods: This was a cross-sectional study conducted at the medical outpatient department in Hospital Port Dickson from January until October 2019. Convenience sampling method was used to recruit potential study participants. Patient satisfaction was measured using Validated Patient Satisfaction with Pharmacist Services Questionnaire (PSPSQ2.0), consisted of quality of care and interpersonal relationship between pharmacist and patient domains. Descriptive data were presented as mean and standard deviation or numbers and percentages, while Independent Sample t-test, ANOVA and post-hoc analysis, and multiple linear regression were used for inferential data analysis. Results: There were 37 (25%) diabetes MTAC, 36 (24.3%) respiratory MTAC, and 75 (50.7%) warfarin MTAC patients recruited. On average, the mean overall satisfaction score was 3.30(SD=0.43). The mean satisfaction score in the interpersonal relationship domain [3.35(SD=0.44)] was higher than the quality of care domain [3.26(SD=0.45)]. There was a significant association between gender, education level, and patient satisfaction towards pharmaceutical care service (p<0.05). Gender and education level statistically predicted respondents' satisfaction with MTAC services (p<0.001). Conclusions: The overall patient satisfaction towards MTAC services in this setting was high. Gender and education level were significant predictors for patient satisfaction. These findings could potentially contribute to the planning of MTAC services in the future.